Effect of boiling on fatty acid composition and tocopherol content of hen, duck, and quail egg oils. Issue 7 (17th May 2019) - Özcan, Mehmet Musa; Al Juhaimi, Fahad; Uslu, Nurhan; Ghafoor, Kashif; Babiker, Elfadil E.; Mohamed Ahmed, Isam A.; Alsawmahi, Omer N.
Abstract: The palmitic acid contents of control groups varied between 22.96% (duck) and 25.09% (hen), while that of boiled egg oils are found between 22.93% (duck) and 23.72% (quail). Oleic acid contents of control group oils changed between 43.04% (quail) and 64.91% (duck) while that of boiled egg oils vary between 43.18% (quail) and 64.17% (duck). Linoleic acid contents of control groups and boiled egg oils changed between 4.34% (duck) and 23.24% (quail) to 5.31% (duck) and 19.81% (quail), respectively. While DL‐α‐tocopherol contents of raw (control) egg oils change between 16.92 mg/100 g (hen) and 26.16 mg/100 g (quail), DL‐α‐tocopherol contents of boiled egg oils were found between 20.47 mg/100 g (hen) and 72.26 mg/100 g (quail). β‐Tocopherol contents of raw egg and boiled egg oils were determined between 8.46 mg/100 g (hen) and 10.41 mg/100 g (duck) to 9.10 (hen) and 13.25 mg/100 g (quail), respectively. γ‐Tocopherol contents of boiled egg oils changed between 3.27 mg/100 g (duck) and 7.43 mg/100 g (quail). Practical applications: Eggs are consumed as breakfast foods, preparation of home meal, and also used as food ingredients. Among eggs from birds, those from hen and duck are the most common and also highly nutritious. Recently, there is an increase in the demand of functional foods by consumers that can prevent several diseases. Egg yolk oils are rich in bioactive compounds like unsaturated fatty acids, pigments, and oil‐soluble vitamins.